Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry